Changes in Neonatal Practice and Temporal Trends in Bronchopulmonary Dysplasia - Dickenson, Georgina; Sikdar, Oishi; Bhat, Ravi; Nanjundapa, Mahesh; Harris, Christopher; Greenough, Anne (American Journal of Perinatology, 2025)
Bronchopulmonary dysplasia (BPD) is the most common adverse outcome of neonatal intensive care and is increasing. Our objective was to determine if temporal trends in BPD were associated with changes in neonatal care practices.The outcomes of infants born at less than 32 weeks of gestation in two study periods, 2012 to 2014 and 2020 to 2022, were compared. The results were divided into those born between 28 and 32 weeks of gestation and less than 28 weeks of gestation. Data were collected from the patient records and an electronic record system, BadgerNet.There were 213 infants and 161 infants in the first and second epoch, respectively; the latter group was of lower gestational age (mean: 28.4 vs. 29.6 weeks, p = 0.03) and birth weight (1,000 vs. 1,124 g, p = 0.01). A greater proportion of the more mature group were growth retarded in the second epoch (23 vs. 12%, p = 0.028). Overall, moderate/severe BPD was higher in the more recent epoch (64 vs. 39%, p < 0.001), but infants were not discharged at a later corrected gestation age, nor was there an increase in use of home oxygen. Mortality, ventilation days, and inotropic support were similar in the two time periods. At all gestations, hydrocortisone use in the first week was higher in the more recent epoch (25 vs. 7%, p < 0.001), as was diuretic use (54 vs. 30%, p < 0.001), paracetamol administration (22 vs. 0%, p < 0.001) and less invasive surfactant administration (41 vs. 0%, p < 0.001). Postnatal dexamethasone use was higher in infants less than 28 weeks of gestation during the most recent epoch (50 vs. 34%, p = 0.034).Over the 10-year period, the BPD incidence increased, likely reflecting that in the latter epoch, infants were more immature and growth retarded. Greater use of hydrocortisone and diuretics was not associated with improved outcomes.
Keywords: prematurity; growth retardation; BPD; PDA; LISA; noninvasive ventilation; hydrocortisone